Correction: Advances in non-enzymatic glucose sensors based on metal oxides. Issue 5 (24th January 2017) - Zhu, Hua; Li, Li; Zhou, Wei; Shao, Zongping; Chen, Xiangjian
Abstract : Correction for 'Advances in non-enzymatic glucose sensors based on metal oxides' by Hua Zhu et al., J. Mater. Chem. B, 2016, 4, 7333–7349.